Profile of science process skills of elementary teacher education students in science learning at primary schools - Fitriyeni; Dea Mustika; Bella Kurnia Sari; Dara Muslimah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
Science process skills are essential for prospective educators today, especially in the subject of IPAS (Integrated Science and Social Studies). The purpose of this study is to describe the science process skills of PGSD (Primary School Teacher Education) students in science learning at elementary schools. This research employs a quantitative descriptive method. The data was obtained through the analysis of student practical assignments in the elementary school science education course involving 113 students in the 2024/2025 academic year. The results of the study show that students achieved an excellent category in the observing indicator (89%); a good category in the questioning and predicting indicators (85%), planning and conducting investigations (80%), and communicating results (80%). However, students were only in the fair category for the processing and analyzing information indicator (72%) and the evaluating and reflecting indicator (75%). This condition is attributed to students not being adequately trained in processing and analyzing information, as well as in evaluating and reflecting on observational results—skills that require critical thinking to connect learned concepts. These findings indicate the need to strengthen learning to train students' critical thinking skills in science education.